2012
DOI: 10.1021/je300279c
|View full text |Cite
|
Sign up to set email alerts
|

Water Content in Biodiesel, Diesel, and Biodiesel–Diesel Blends

Abstract: Biodiesel has a higher affinity toward moisture content than petroleum diesel, and the water retaining capacity of biodiesel is higher than diesel. The water content in fuels can be classified in free, emulsionated, and soluble water. High water content in biodiesel and diesel can cause problems such as water accumulation and microbial growth in fuel tanks and transportation equipment. Currently, there is a lack of information on water absorbance in biodiesel and biodiesel/diesel blends. Experiments were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 10 publications
4
49
0
2
Order By: Relevance
“…The presence of water may further lead to formation of sludge and slime which could result in blockage of fuel filters and fuel lines thereby damaging vehicles fuel injection systems. The solubility of water is dependent on the temperature and composition of fuel [156]. Wu et al [157] reported biodiesel obtained from Trichosporon capitatum to have a better cold filter plugging point (CFFP).…”
Section: Characterization Of Biodiesel and Their Fuel Propertiesmentioning
confidence: 99%
“…The presence of water may further lead to formation of sludge and slime which could result in blockage of fuel filters and fuel lines thereby damaging vehicles fuel injection systems. The solubility of water is dependent on the temperature and composition of fuel [156]. Wu et al [157] reported biodiesel obtained from Trichosporon capitatum to have a better cold filter plugging point (CFFP).…”
Section: Characterization Of Biodiesel and Their Fuel Propertiesmentioning
confidence: 99%
“…Although higher heating value (HHV) is widely applied in combustion practices, lower heating value (LHV) is usually used in estimation models of automotive fuel and engine performance due to negligible amount of water vapor produced from such fuel [27,28]. Hence, LHV of blended marine fuel with biodiesel is computed and discussed in this study.…”
Section: Lower Heating Value (Lhv)mentioning
confidence: 99%
“…This is due to the fact that automotive fuels contain only small amount of water (<0.05% by mass) which can be neglected during heating value estimation [16], [17].…”
Section: Introductionmentioning
confidence: 99%